Secured Multikeyword Search over Encrypted Cloud Data Based On Quality and Usability - B.Ananthi, S.V.Priyadharshini, M.Ramesh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Searchable encryption permits to upload encrypted documents to a remote honest-but-suspicious server and query that data at the server without the papers having to be decrypted first. With the advent of cloud computing, data owners are encouraged to move their sophisticated data management systems from local sites to commercial public clouds for greater flexibility and cost savings. However, in order to safeguard data privacy, sensitive data must be encrypted before being outsourced, rendering traditional data utilization based on plaintext keyword search outdated. As a result, implementing an encrypted cloud data search service is critical. Given the huge number of data users and documents in the cloud, it is critical for the search service to support multi-keyword queries and result similarity ranking in order to meet the effective data retrieval requirement. In this paper propose the Secured Multikeyword Search over Encrypted Cloud Data, which is based On Quality and Usability of cloud data transmission and storage. Further we used triple DES (Data Encryption Standard) Algorithm of encryption and decryption key for secure authentication process. Here we used different key sizes are used in cryptographic process. Our analysis shows that the suggested approach is secure against adaptive chosen-keyword attacks. This solution is highly efficient and ready to be applied in real-world cloud storage systems, and it also achieves better encryption and decryption execution speed. .